2009
DOI: 10.1097/mop.0b013e3283325e3a
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal innate immunity in allergy development

Abstract: Dose, site and timing of allergen exposure are likely to modulate the innate immune response, polarizing the maturing neonatal immune system towards Th1 or Th2-type responses, thereby protecting from or predisposing to asthma and allergies. Modulation of neonatal innate immune responses may be a novel approach to prevent asthma and allergies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 77 publications
2
44
0
6
Order By: Relevance
“…This is likely due to many factors, including, but not limited to, Th2-skewed immune responses in neonates (1, 2, 4, 22), impaired B and T cell function or recruitment (6,21,33), and defects in dendritic cell maturation and recruitment to the lung (13,28). In this study, viral loads were significantly higher in the lungs of neonates than in those of adult mice at 7 and 14 dpi (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is likely due to many factors, including, but not limited to, Th2-skewed immune responses in neonates (1, 2, 4, 22), impaired B and T cell function or recruitment (6,21,33), and defects in dendritic cell maturation and recruitment to the lung (13,28). In this study, viral loads were significantly higher in the lungs of neonates than in those of adult mice at 7 and 14 dpi (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In line with impaired Th1 responses, Th2 immunity is thought to be dominant in neonatal mice (2,22). The increased susceptibility of neonates has also been attributed to factors such as a lack of preexisting memory and both a low frequency and impaired function of effector B and T cells (6,21,33) along with impaired dendritic cell maturation and recruitment to the lung (13,28). Differences such as these may help to explain why a variety of respiratory viruses, including respiratory syncytial virus (RSV), influenza virus, adenoviruses, and others, cause substantial disease in infants (11,27,32).…”
mentioning
confidence: 99%
“…In support, the spontaneous wave of type 2 immunity around PND14 was intact in Rag2-deficient mice, and ILC2 accumulations were even enhanced in these mice, most likely due to increased availability of IL-2 in Rag2 À/À mice. Studies in neonatal rodents and humans reported scarcity as well as immaturity of pulmonary DCs, hyporesponsiveness to PAMPs, and low lymphocyte numbers and therefore suggested incompetence of the early postnatal pulmonary immune system to mount adaptive immune responses, an effect that was even exacerbated in germ-free mice (Belderbos et al, 2009;Gollwitzer et al, 2014;Nelson and Holt, 1995;Nelson et al, 1994;Roux et al, 2011;Tschernig et al, 2006). In accordance with these studies, we found that DCs were indeed severely impaired in neonatal lungs, and the few CD11b + DCs in neonatal lungs during the first post-natal week were sessile CD11b + CD64 + moDCs that closely resemble macrophages Plantinga et al, 2013).…”
Section: (Legend Continued On Next Page)mentioning
confidence: 99%
“…Antigen-presenting cells in neonates show weaker responses to innate stimuli than do those in adults, except for Toll-like receptor (TLR)-mediated responses to TLR8 agonists [16]. TLR agonists generally promote Th1 development and have been therapeutically developed to prevent and treat allergic diseases, albeit with conflicting results [17]. The effect of innate immune responses on the onset of allergies depends on the timing, dose and site of stimulation [18].…”
Section: Early Immune Maturation and Respiratory Healthmentioning
confidence: 99%
“…The lung develops in five phases: the embryonic period (up to week 6), the pseudoglandular period (weeks 6-16), the canalicular period (weeks [16][17][18][19][20][21][22][23][24], the saccular period (weeks 24-40) and the alveolarisation period (which takes place mostly after birth) [133]. Preterm babies born before the 32nd week of gestation have lungs in the saccular stage of development at birth.…”
Section: Long-term Consequences Of Prematurity and Bpdmentioning
confidence: 99%